GENDER RELATIONS AND ITS IMPACT ON THE ECONOMY OF OLAMABORO 1960 - 2020 - PROFFESSOR M.S. AUDU; DR ROSELINE MORENIKE OSHEWOLO; PRECIOUS OMANYO ATI (International Studies Journal)
This study explores Gender Relations and Its Impact on the Economy of Olamaboro, examining how traditional gender roles and expectations influence economic participation and development within the community. Through qualitative method, the research analyzes the contributions of both men and women to local economic activities, highlighting disparities in access to resources, education, and employment opportunities. Findings reveal that gender relations significantly affect economic outcomes, with women facing systemic barriers that limit their participation in key economic sectors. The study recommends policies aimed at promoting gender equity and empowering women to enhance overall economic growth in Olamaboro. By addressing these gender imbalances, the community can harness the full potential of its population, leading to sustainable development and improved economic resilience. This work contributes to literature on gender and economic history by shedding light on community level experiences and advocating for inclusive policies that promote gender equity in the local economies.